DIGITAL-NATIVE WORKFORCE: STRATEGI PENGEMBANGAN SDM UNTUK GENERASI Z - Ekasani, Deva; Kuswinarno, Mudji (Kohesi: Jurnal Sains dan Teknologi, 2024)
Generation Z, who grew up in the digital era, must be able to adapt to the rapid development of technology and even bring unique characteristics to the world of work as a digital native workforce. As a generation that is technologically savvy and has different work preferences, an adaptive and innovative strategy is needed in managing human resources (HR) for Generation Z. This article "Digital-Native Workforce: HR development strategies for Generation Z" discusses the importance of understanding the characteristics of Generation Z, such as their needs, mindsets, and expectations of the work environment. In addition, Generation Z needs an effective HR development strategy, including technology-based training, collaborative approaches, strengthening soft skills, and using digital platforms in talent management. By implementing this strategy, organizations can create an inclusive and productive work environment, and maximize the potential of Generation Z as an important part of the modern workforce. This article aims to provide practical insights for HR managers and leaders in managing and developing a dynamic generation of workers in the era of digital transformation. Generasi Z yang tumbuh di era digital, harus mampu beradaptasi terhadap pesatnya perkembangan teknologi bahkan membawa karakteristik unik ke dunia kerja sebagai digital native workforce. Sebagai generasi yang mahir teknologi dan memiliki preferensi kerja yang berbeda, dibutuhkan strategi yang adaptif dan inovatif dalam pengelolaan sumber daya manusia (SDM) untuk Generasi Z. Dalam artikel “Digital-Native Workforce: Strategi pengembangan SDM untuk Generasi Z” ini membahas terkait pentingnya memahami karakteristik Generasi Z, seperti kebutuhan, pola pikir, serta ekspektasi mereka terhadap lingkungan kerja. Selain itu, Generasi Z membutuhkan strategi pengembangan SDM yang efektif, termasuk pelatihan berbasis teknologi, pendekatan kolaboratif, penguatan soft skills, dan penggunaan platform digital dalam manajemen talenta. Dengan menerapkan strategi ini, organisasi dapat menciptakan lingkungan kerja yang inklusif dan produktif, serta memaksimalkan potensi Generasi Z sebagai bagian penting dari tenaga kerja modern. Artikel ini bertujuan memberikan wawasan praktis bagi manajer dan pemimpin HR dalam mengelola dan mengembangkan generasi pekerja yang dinamis di era transformasi digital.